The impact of transient visual deprivation and proprioception in motor skill learning and acute cortical excitability - Nätkynmäki, Anna (2020)
The purpose of the present study was to assess the impact of transient visual deprivation in complex motor skill learning and motor skill training induced acute cortical excitability in healthy subjects. Training induced alterations in proprioception was another field of interest investigated in this study. The study investigated three separate training conditions induced motor cortex plasticity effects with transcranial magnetic stimulation. Training conditions used in this study were eyes open, eyes closed and imaginary training. Imaginary training was added to clarify the effect of eyes closing motor skill training. The motor skill training was performed with tibialis anterior muscle as ankle dorsiflexion movement. Transcranial magnetic stimulation (TMS) was the main method of investigation of the cortical site plasticity. With TMS, motor skill training induced plasticity changes were researched as altered motor evoked potentials elicited from the tibialis anterior cortical area. With single-pulse TMS, the I/O curve represented the excitability changes and strength of the corticospinal tract. Paired-pulse TMS elicited SICI represents the inhibitory phenomenon in the motor cortex. Spinal level excitability changes were assessed with peripheral electrical stimulation. Maximal H-reflex of tibialis anterior represented spinal reflex pathway excitability alterations. The motor skill training was performed with the right ankle as a force-time curve, with separate emphasis of force and rhythm aspects. The development in 20 minutes (40 trials) of motor skill training was largest in eyes open training condition. Imaginary training condition had indications of the largest change in the rhythm part. Transient visual deprivation protocol showed indications of increased excitability in every I/O curve intensity and a significant increase was observed after imaginary training. The intracortical inhibition indicated to reduce after training performed with transient visual deprivation protocol. However, the change was not significant. Spinal excitability showed a lack of statistical support, but indications of the reflex pathway alterations were observed in the imaginary training condition. Eyes open training pre value in proprioception was significantly less compared to imaginary training and post values did not differ significantly. Eyes open showed indications of the largest change. The results indicate that vision acts as a dominant sense in motor skill learning, but it also seems that sensorimotor training affects the learning process. The excitability of the corticospinal tract seemed to increase when the motor skill training was performed with transient visual deprivation protocol, and imaginary training had a significant effect. The probable reason behind non-visual processing might arise from the change between cortical level performance or learned focused attention. The results indicate that change in motor skill training performed with transient visual deprivation might be acquired via compensated mechanisms, such as enhanced corticospinal level excitability, decreases in the intracortical inhibition, and proprioceptive feedback processing. Indications of acquired accuracy and rhythm after imaginary training was showed, but the speed of performance seemed more related to physically performed training. A probable explanation for the development in this type of motor skill training might lie in increased connection efficacy in existing synapses, motor cortex representation area expansion, and enhanced proprioceptive processing.